Increasing the Added Value of Water Clover (Marsilea Drummondii l.) in Wonosari Village, Mojokerto Regency into Cookies: Peningkatan Nilai Tambah Semanggi Air (Marsilea Drummondii l.) di Desa Wonosari Kabupaten Mojokerto menjadi Cookies - Puspitasari, Kiki Candra; Pebrianggara, Alshaf; Hindarto; Sholikhah, Imroatus; Ni’mah, Alfa (Universitas Muhammadiyah Sidoarjo, 2022)
Water clover (Marsilea Drummondii L) is a type of fern that grows in lakes, swamps and rice fields. Water clover has a very distinctive morphology, namely the shape of a leaf that resembles an umbrella composed of four opposite leaf petals (Nurjanah et al, 2012: Afriastini 2003). Water clover contains phytochemicals in the form of reducing sugars, steroids, carbohydrates, and flavonoids (Jacoeb et al, 2010), antioxidants (Nurjanah et al, 2012). In addition, water clover has a moisture content of 82.59%, ash 1.72%, protein 1.91%, fat 0.36%, carbohydrates 11.46%, and crude fiber 1.96% (Nurjanah et al, 2012) . In the Mojokerto area, precisely in Wonosari Village, Ngoro District, Mojokerto Regency, it is also famous for clover which is usually processed into clover pecel. Pecel clover is usually sold in one of the tours owned by the village, namely Sumber Dhuwur. Therefore, after we know that water clover is a functional food and so that clover has added value for sale, we make an innovation. This water clover will be used as Cookies. From this innovation, it is hoped that people will be more interested in buying products from clover and sellers will increase their income